Weton Divination in Javanese Marriage: An Archetypal Study in Ngadiluwih, Kediri - Dinso, Junio Boy Smara; Waryanti, Endang; Muarifin, Moch. (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
This study explores the cultural role of weton, a traditional Javanese calendrical system, in determining auspicious marriage dates in Ngadiluwih, Kediri. Using a Jungian archetypal framework and qualitative descriptive methods, data were collected through interviews with two adat leaders and observations of local wedding rituals. The findings reveal that favorable weton pairings such as Sunday Legi and Friday Wage embody archetypes of harmony (tentrem), affection (jodo), and social cohesion (rukun). In contrast, combinations like Tuesday Kliwon and Wednesday Wage reflect shadow archetypes associated with conflict (pegat), hardship (mlarat), and emotional distress (sengsara). These patterns function as cultural symbols rooted in the collective unconscious, guiding moral and practical choices in marriage. The study highlights weton as a living symbolic system and proposes its integration into cultural education and heritage preservation programs.